Effect of prasugrel in patients with asthma: results of PRINA, a randomized, double‐blind, placebo‐controlled, cross‐over study. (16th December 2014) - Lussana, F.; Di Marco, F.; Terraneo, S.; Parati, M.; Razzari, C.; Scavone, M.; Femia, E. A.; Moro, A.; Centanni, S.; Cattaneo, M.
Summary Background Although experimental studies have demonstrated that platelets are proinflammatory cells, no randomized studies have tested the anti‐inflammatory effect of antiplatelet agents in humans. The platelet P2Y12 receptors mediated bronchial inflammation in a mouse model of asthma, suggesting that P2Y12 represents a pharmacologic target for asthma. Objectives In this proof‐of concept, placebo‐controlled, randomized, cross‐over study, we tested the effects of the P2Y12 antagonist prasugrel on bronchial hyperreactivity of asthmatic patients. Patients/Methods Twenty‐six asthmatic patients were randomly and blindly allocated to prasugrel (10 mg once daily) or placebo for 15 days. After a ≥ 15‐day wash‐out, patients were crossed over to the alternative treatment. Before and after each treatment, patients underwent a bronchial provocation test with mannitol and measurement of fractional exhaled nitric oxide (FeNO). Inhibition of P2Y12‐dependent platelet reactivity (platelet reactivity index [PRI]) was measured with the vasodilator‐stimulated phosphoprotein phosphorylation assay. Results The provocative dose of mannitol causing a 15% drop in forced expiratory volume in 1 s increased from 142 mg (95% confidence interval [CI] 82–202) to 187 mg (95% CI 113–262) after prasugrel treatment (P = 0.09), and did not change after placebo treatment (136 mg [95% CI 76–196] and 144 mg [95% CI 84–204], P = 0.65). FeNO did not change after either treatment. The PRI decreased from 80% (95% CI 77–83) to 23% (95% CI 7–29) after prasugrel treatment (P < 0.001) and remained unchanged after placebo. Conclusions Our proof‐of‐concept, randomized, controlled study is the first one to test in vivo the anti‐inflammatory effects of platelet inhibition in human patients. The results suggest that pharmacologic inhibition of P2Y12 receptors may slightly reduce the bronchial inflammatory burden, and lay the groundwork for further studies, with clinical endpoints.